2016
DOI: 10.1038/hr.2016.53
|View full text |Cite
|
Sign up to set email alerts
|

Increased neuronal seizure activity correlates with excessive systemic inflammation in a rat model of severe preeclampsia

Abstract: Preeclampsia (PE), one of the most common disorders of pregnancy, is characterized by hypertension and albuminuria. In severe cases, PE results in eclampsia-like seizures. Studies have suggested that severe PE is related to an exaggerated systemic inflammatory response, which may increase sensitivity to seizures. In the current study, we investigated whether the seizure activity of neurons was enhanced under excessive systemic inflammation. We also sought to determine whether MgSO could reduce the effects of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Based on the classical PE models (LPS infusion) established by Fass et al [ 21 ], we used intraperitoneal injection of PTZ (40 mg/kg body weight) to induce seizures to set an eclampsia-like model to be used in the subsequent studies in order to fully investigate the mechanisms underlying PE and E, and we would try to apply other models. By using PTZ-induced rat models, our previous studies suggested that excessive systemic inflammation and increased brain inflammation in pre-eclampsia decreased the eclampsia-like seizure threshold [ 22 , 39 ], and seizures further increased brain inflammation [ 5 ]. We also found that the number of activated microglia cells and astrocytes in the CA1 area was higher in the pre-eclampsia group than in the normal pregnancy group; this number continued to increase in the eclampsia group [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the classical PE models (LPS infusion) established by Fass et al [ 21 ], we used intraperitoneal injection of PTZ (40 mg/kg body weight) to induce seizures to set an eclampsia-like model to be used in the subsequent studies in order to fully investigate the mechanisms underlying PE and E, and we would try to apply other models. By using PTZ-induced rat models, our previous studies suggested that excessive systemic inflammation and increased brain inflammation in pre-eclampsia decreased the eclampsia-like seizure threshold [ 22 , 39 ], and seizures further increased brain inflammation [ 5 ]. We also found that the number of activated microglia cells and astrocytes in the CA1 area was higher in the pre-eclampsia group than in the normal pregnancy group; this number continued to increase in the eclampsia group [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Shielded, low-weight, flexible cables, connecting the electrodes to the input dual bioamplifier (ml408; dbs337) was attached to examined rat. EEG was recorded on signal channel (channel1:source channel) with low-frequency filter (LFF) of 0.1 Hz and high-frequency filter (HFF) of 60 Hz with sampling rate of 1 KHz (Liu et al, 2016).…”
Section: Recording Electroencephalogram (Eeg)mentioning
confidence: 99%
“…It is interesting that a study using an ex vivo placental perfusion system showed that IL‐1β and IL‐1Ra secretion into maternal circulation is increased in PE and is attenuated after the administration of MgSO 4 , proposing thus a possible mechanism of action of this anticonvulsive agent in the disease . The same effect was also observed in a study of a lipopolysaccharide (LPS)‐treated rat model of PE, which indicated that serum levels of IL‐1β were elevated in preeclamptic pregnancies and decreased significantly after treatment with MgSO 4 …”
Section: Resultsmentioning
confidence: 71%